Ammonia-induced excess ROS causes impairment and apoptosis in porcine IPEC-J2 intestinal epithelial cells - Yihao Huang; Shangkun Mo; Yi Jin; Zhuoning Zheng; Hanyi Wang; Shaojuan Wu; Zhuqing Ren; Jian Wu (Ecotoxicology and Environmental Safety, 2022)
Ammonia is one of the most important toxic metabolites in the intestine of animals. It can cause intestinal damage and associated intestinal diseases through different endogenous or exogenous stimuli. However, the definition of harmful ammonia concentration and the molecular mechanism of ammonia - induced intestinal epithelial injury remain unclear. In this study, we found that the viability of porcine IPEC-J2 intestinal epithelial cells significantly decreased with the increase of NH4Cl dose (20–80 mM). Ammonia (40 mM NH4Cl) increased the expression level of ammonia transporter RHCG and disrupted the intestinal barrier function of IPEC-J2 cells by reducing the expression levels of the tight junction molecules ZO-1 and Claudin-1. Ammonia caused elevated levels of ROS and apoptosis in IPEC-J2 cells. This was manifested by decreased activity of antioxidant enzymes SOD and GPx, decreased mitochondrial membrane potential, and increased cytoplasmic Ca2+ concentration. In addition, the expression levels of apoptosis-related molecules Caspase-9, Caspase-3, Fas, Caspase-8, p53 and Bax were increased, the expression level of anti-apoptotic molecule Bcl-2 was decreased. Moreover, the antioxidant NAC (N-acetyl-L-cysteamine) effectively alleviated ammonia-induced cytotoxicity, reduced ROS level, Ca2+ concentration, and the apoptosis of IPEC-J2 cells. The results suggest that ammonia-induced excess ROS triggered apoptosis through mitochondrial pathway, death receptor pathway and DNA damage. This study can provide reference and theoretical basis for the definition of harmful ammonia concentration in pig intestine and the effect and mechanism of ammonia on pig intestinal health.